Wolbachia variability and host effects on crossing type in Culex mosquitoes. - Sinkins, S; Walker, T; Lynd, A; Steven, A; Makepeace, B; Godfray, H; Parkhill, J (2005)
Wolbachia is a common maternally inherited bacterial symbiont able to induce crossing sterilities known as cytoplasmic incompatibility (CI) in insects. Wolbachia-modified sperm are unable to complete fertilization of uninfected ova, but a rescue function allows infected eggs to develop normally. By providing a reproductive advantage to infected females, Wolbachia can rapidly invade uninfected populations, and this could provide a mechanism for driving transgenes through pest populations. CI can also occur between Wolbachia-infected populations and is usually associated with the presence of different Wolbachia strains. In the Culex pipiens mosquito group (including the filariasis vector C. quinquefasciatus) a very unusual degree of complexity of Wolbachia-induced crossing-types has been reported, with partial or complete CI that can be unidirectional or bidirectional, yet no Wolbachia strain variation was found. Here we show variation between incompatible Culex strains in two Wolbachia ankyrin repeat-encoding genes associated with a prophage region, one of which is sex-specifically expressed in some strains, and also a direct effect of the host nuclear genome on CI rescue.